A systematic review on cultural context, time orientation, and power distance in ICT-mediated collaborative learning in higher education - Zhai, Chunpeng; Wibowo, Santoso; Viriyavejakul, Chantana; Rahman, Shaikh Sadik (My University, 2026)
Information and communication technologies (ICTs) encompass the use of digital tools including computers, mobile devices, online platforms, and interactive software for enhancing communication, learning, and productivity. Most studies focus on participation, communication, and learning experience, leaving a critical gap in understanding how intercultural constructs shape digital engagement and learning outcomes in multicultural ICT-mediated contexts. Many digital learning environments continue to reflect Western-centric assumptions about monochronic time management, communication patterns, and learner autonomy, which can marginalize students from high-context or polychronic cultural backgrounds. This systematic review examines three underrepresented cultural dimensions: Hall’s high- and low-context communication styles, which explain differences in direct and indirect communication; polychronic–monochronic time orientations, which explain differences in flexible and linear approaches to time; and Hofstede’s concept of power distance, which explains differences in expectations about authority and participation in ICT-supported higher education. The review seeks to identify the broader patterns through which these cultural factors influence access to information, digital literacy, communication, collaboration, and learning behavior in multicultural digital environments. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 22 relevant articles were retrieved from ProQuest, IEEE Xplore, ScienceDirect, Web of Science, and Google Scholar databases. The findings indicate that these cultural dimensions shape how students participate in ICT-supported learning, with many digital environments implicitly favoring low-context communication, monochronic time management, and low-power-distance interaction norms. This may place additional organizational and cognitive demands on students from other cultural orientations, although current evidence remains limited regarding whether culturally responsive adaptations improve academic performance as distinct from participation and learning experience.
Keywords: high-context and low-context communication; ICTs; polychronic and monochronic time orientation; power distance; students